Proposed design of prosthetic arm with the integration of Kano model and TRIZ method - Hapsoro Agung Jatmiko; Azmi Nur Dyah Rahmaningtyas; Fatma Hermining Astuti (OPSI, 2026)
Individuals with upper-limb disabilities face substantial limitations in performing daily activities. Statistics Indonesia reports that 62.59% of persons with disabilities have physical impairments, while the Special Region of Yogyakarta ranks among the three provinces with the highest prevalence of finger and hand mobility disorders, at 0.44%. However, most available prosthetic devices remain primarily cosmetic and provide limited functional performance, leaving users’ needs and expectations unmet. This study aims to design a functional prosthetic hand that addresses user requirements and expectations by integrating the Kano model and the TRIZ (Teoriya Resheniya Izobretatelskikh Zadatch) method. The Kano model was applied to identify and classify user needs based on satisfaction levels, involving 15 individuals with upper-limb disabilities in Gunungkidul Regency. TRIZ was subsequently used to develop systematic and innovative design solutions. The proposed design emphasizes functionality, comfort, safety, ergonomics, ease of use, product quality, and aesthetic appearance. The design was validated through feedback from users and experts. Of the 13 respondents involved in the validation process, 11 agreed with the proposed design, while two recommended minor revisions to accommodate specific disability conditions. The final design consists of two prosthetic configurations: transhumeral and transradial prosthetic hands.